Implicações dos resultados da Prova Brasil na organização do sistema escolar de Mato Grosso para a melhoria da qualidade do processo ensino aprendizagem da matemática no ensino fundamental - Silva, Marta Andreia Estancare Pinheiro (2016)
Our research aims to investigate the Prova Brasil results in organizing the school system of Mato Grosso for the improvement of the quality of teaching-learning process of Mathematics in elementar school. Considering the nature of this study, the research methodology adopted was the qualitative. It had as context the Secretaria de Estado de Educação [State Department of Education], the Centro de Formação e Atualização dos Profissionais da Educação Básica de Mato Grosso [Center for Training and Professional Updating of Basic Education of Mato Grosso] and four state-run public schools, in Cuiabá/MT city. As a partaker of the research we had one Technical of the Superintendence of Elementary Education of SEDUC/MT, two trainers in Mathematics área of CEFAPRO of Cuiabá, the management team (Director and Pedagogical Coordinator) and the school teachers working in the 5th and 9th years in the selected schools. For the production of the data we use the following procedures and instruments: questionaries, semistructured interviews, files supplied by SEDUC/MT and by the CEFAPRO of Cuiabá, as well as the Political Pedagogical Project offered by the schools. For the analyses and interpretation of the datas produced we elected three cathegories: Prova Brasil (Brazil Test), while evaluative instrument to educational level of Elementary School, with the possibility to point out ways and discussions for school quality; Conceptions of quality expressed by the subjects in the dimensions: Intra-school and extra-school and school Organization of Human Training Cycle. The analysis of the data, of the implications of Prova Brasil results, in the investigated contexts, expressed in the speeches of the participants, indicates there are fragilities in the conception of the potentiality of the external evaluation as propiciator of discussions and actions to improving the quality of the teaching-learning process of Mathematics in elementary education. It also shows the disarticulation of guidelines and proposals towards schools, by the governing bodies once SEDUC/MT and CEFAPRO in Cuiabá, allege limited performance due to the reduced staff. Besides this, the data show that the results of Prova Brasil are not released to the whole scholar community, limiting it to the school teachers, which has contributed little to the promotion of articulated plans aiming the advance of proficiency in mathematics of students in this educational phase. The analysis of the education quality and of the teaching-learning process of Mathematic points out that the quality relates to the perspective of the intra-school dimension, as in the system level: the educational supply conditions, the guarantee of adequate installations, as to the teacher level: title/proper qualification to professional practice. Regarding the analysis of the Organization of Human Formation in Cycle, we found by the speeches of the partakers that the majority, allege great dissatisfaction and demotivation, compromising its pedagogical practice. It happens, in our opinion, due to the lacking comprehension of the fundamentals of the Humano Formation in Cycles. Others, however, transfer the whole guilty to the low results in the Prova Brasil to the automatic progression, and to the disengagement of the articulator teacher, without, yet reflect that the teaching-learning process, in any school organization, is also of their responsibility.